2021
DOI: 10.21203/rs.3.rs-1071095/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The Therapeutic Value of Volumetric-Modulated Arc Therapy In Advanced Non-Small Cell Lung Cancer Primary Tumors: A Multicenter Retrospective Analysis Based On Propensity Score Matching And Comparison With Intensity-Modulated Radiotherapy

Abstract: Objective:.To explore the feasibility of volumetric-modulated arc therapy (VMAT) instead of intensity-modulated radiotherapy (IMRT) for primary tumors of advanced non–small-cell lung cancer (A-NSCLC). Methods:.We used propensity score matching (PSM) and multicenter retrospective analysis to study the efficacy and toxicity of VMAT technology in radiotherapy for primary tumors of A-NSCLC.We used the chi-squared test to analyze the response rate(RR), local control (LC), acute radiation injury, and dose-volume par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 18 publications
0
1
0
Order By: Relevance
“…A post hoc analysis by Chen et al, regarding radiation treatment technique in RTOG 0617 observed that while survival is similar between patients receiving IMRT vs. 3D-CRT, IMRT was associated with significantly lower rates of severe pneumonitis and cardiac doses. Additionally, Liu et al further reported that the use of VMAT led to significantly lower dose-volume parameters in normal tissue while achieving similar efficacy compared to IMRT (Chun et al 2017 ; Liu et al 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…A post hoc analysis by Chen et al, regarding radiation treatment technique in RTOG 0617 observed that while survival is similar between patients receiving IMRT vs. 3D-CRT, IMRT was associated with significantly lower rates of severe pneumonitis and cardiac doses. Additionally, Liu et al further reported that the use of VMAT led to significantly lower dose-volume parameters in normal tissue while achieving similar efficacy compared to IMRT (Chun et al 2017 ; Liu et al 2021 ).…”
Section: Discussionmentioning
confidence: 99%